A vulnerability index based-approach for the historical centre of the city of Latronico (Potenza, Southern Italy). (June 2022) - Chieffo, N.; Formisano, A.; Landolfo, R.; Milani, G.
Highlights: The vulnerability index assessment method was extended to the historical centre made up of typical masonry aggregates. The CARTIS methodology was applied for the inventory of the predominant structural typologies in the investigated area. A damage scenario was obtained using a proper intensity prediction equation. A simplified methodological approach was provided for the evaluation of the expected losses. A set of fragility curves for masonry compounds was derived. Abstract: The research aims to illustrate a vulnerability approach extended for the aggregate masonry buildings belonging to an urban area of the city of Latronico (Basilicata Region). The area was examined taking into account the predominant building typology according to the investigation line WP2 " Inventory of existing structural typology " of the Italian ReLUIS project. The propensity at damage of the masonry stock was done according to a survey form conceived for clustered typologies. A damage scenario was provided according to the hazard map concerning the study area. To this purpose, three seismic events were evaluated with variable magnitudes and epicentre distances, by adopting a seismic intensity prediction equation. Fragility curves were estimated relating the macroseismic observation to the PGA, providing an overview of the asset exposed at risk. The achieved outcomes were discussed in relation to the fragility functions concerning the BTM, highlighting the differences in terms of the expected damage.